IMPLEMENTASI TUGAS PENGHULU TERKAIT PEMBANGUNAN JALAN PEDESAAN BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 84 TAHUN 2015 TENTANG SUSUNAN ORGANISASI DAN TATA KERJA PEMERINTAHAN DESA DI KAMPUNG DAYUN KECAMATAN DAYUN KABUPATEN SIAK PROVINSI RIAU - Syahputra, Julpan; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The implementation of road construction is the most basic means that aim to support the smooth running of human transportation networks. The welfare of the community can be seen from the physical condition of the area regarding the facilities provided by the government. Building village independence within the village framework must begin with a good village planning process, and be followed by good program governance as well. Effective rural development is not merely an opportunity but the result of determining priority choices for good planning activities. The village government as the lowest government unit plays a frontline role in governance and development. In the Regulation of the Minister of Home Affairs Number 84 of 2015 concerning the Organizational Structure and Work Procedure of Village Administration, Article 6 paragraph (2) states that "The village head is in charge of organizing village governance, implementing development, community development and community empowerment".This type of research is juridical empirical research or sociological legal research, namely a research approach that emphasizes the legal aspects relating to the subject matter to be discussed, linked to the reality in the field. This research was conducted at the Office of the Pengulu Kampung Dayun and the Office for Community Empowerment and the Village of Siak Regency, while the sample population is all parties related to the problem under study. Sources of data used are primary data and secondary data, data collection techniques in this study are by observation, questionnaires, interviews and literature review.In the research results, there are three main points that can be concluded. First, the implementation of the duties of the village head regarding the construction of rural roads has not been carried out properly. The two inhibiting factors in rural road development are budgetary factors, delays in the implementation of village funds, coordination of related parties, and rarely conducting village meetings. The three future efforts made by the village head in rural road development are the need to plan village development and use local resources.Keywords: Implementation - Development - Rural Roads